Peningkatan Kualitas Pendidikan Melalu Penerapan E-Learning - Dedi Kurniawan; Siti Fatimah (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2021)
Along with the development of the era of globalization, the education system around the world has also undergone changes, especially regarding the learning of students. Recently, developments have started from the online learning system or E-Learning. Or have begun to change because of the increasingly growing digital platforms. Meanwhile, the e-learning industry in Indonesia has not been able to develop better. The main objective of this study is to understand the barriers to implementing e-learning in Indonesia apart from the benefits of online education, such as lower costs and pedagogical benefits. The researcher proposes an initial conceptual framework that explains the steps and intentions of students to switch to utilizing e-learning. In our future research, researchers will refine and test conceptual frameworks and provide guidelines for higher education institutions and policy makers on institutional change to support the use of e-learning.